Analisis Tingkat Kepuasan Konsumen Food Truck di Yamaha Land Surabaya - Natasya Fadilah; Sigit Dwi Nugroho; Dona Wahyuning Laily (Universitas Batanghari Jambi, 2023)
Yamaha Land is a place of business for food truck entrepreneurs who were born in Surabaya. Customer satisfaction is important for the company because it can also be a marketing tool. One effort to increase consumer satisfaction is to determine the level of consumer preference for the characteristics of a product or service. The purpose of this study was to determine the characteristics of consumers, the process of consumer purchasing decisions, and customer satisfaction at Yamaha Land Surabaya. The number of respondents in the study were 96 respondents. The analytical methods used in this research are descriptive analysis, Importance Performance Analysis (IPA), and Customer Satisfaction Analysis (CSI). Based on the results of the study, it can be seen that the majority of Yamaha Land consumers are male, with an age range of 22-27 years, monthly income of Rp. Yamaha Land consumers go through five stages in their purchase decision process, namely the need recognition stage, information search, alternative evaluation, purchase decision and post-purchase. The results of Importance Performance Analysis (IPA) of attributes contained in quadrant I are taste and speed, Quadrant II is cleanliness, friendliness, politeness, and tidiness, Quadrant III is price, color and texture, and Quadrant IV is aroma. While the value on the Customer Satisfaction Index (CSI) is 75.6 percent. Judging from the consumer satisfaction index, it can be said that consumers who come to Yamaha Land for all tested attributes are in the satisfied category.